Determinants of SME Finance: Evidence from Three Central European Countries - Ashiqur Rahman; Jaroslav Belas; Twyeafur Rahman M. (Review of Economic Perspectives, 2017)
This paper explores the determinants of access to finance for small and medium enterprises (SMEs) in the context of three Central European countries: Czech Republic, Slovak Republic, and Hungary. The data set of the research is obtained from the BEEPS survey, which is conducted by the World Bank and the European Bank for Reconstruction and Development. This paper empirically analyses firms not only from the SMEs point of view, but also shows results for micro, small and medium enterprises separately. Additionally, we have analysed the determinants of access to finance for SMEs at each country level for an in-depth understanding of country-level variations in SME financing. The results indicate that micro firms and firms owned and operated by women are experiencing a shortage of credits from banks. On the other hand, we found a positive relationship between the pledge of collateral and access to finance. With respect to the medium firms, we found evidence that innovative firms have a larger amount of credit from banks. The empirical results also suggest that the loan size increases as the interest rates increase in particular for SMEs on the whole and for micro-firms, although the interest rate is in a negative relationship with the loan size in Czech Republic.
Keywords: G21; O16; 330; Access to finance; SMEs; Czech Republic; Slovak Republic; Hungary